Identification of the Apa protein secreted by Mycobacterium avium subsp. paratuberculosis as a novel fecal biomarker for Johne's disease in cattle - da Silva de Souza, Giliane (2018)
Paratuberculosis (PTB) or Johne's disease is a chronic intestinal infection of ruminants, caused by Mycobacterium avium subsp. paratuberculosis. The shedding of mycobacteria in the feces starts at the initial stages and increases with disease progression, suggesting that antigens secreted by mycobacteria could be excreted in the feces. Previously, we demonstrated that the alanine and proline-rich antigen (Apa), a secretory antigen of Map, could be detected in the intestine of cows with PTB using a monoclonal antibody. In this study, we verified whether this protein can be found in consistently detectable levels in the feces of cattle with PTB. Feces were obtained from cows with Johne's disease confirmed by laboratory tests, cows with suspected PTB based on seropositivity and from PTB-free control cows. Samples were immunoprecipitated using anti-Apa monoclonal antibody and analyzed by immunoblot. The Apa was detected as a 60/70 kDa doublet band in all samples obtained from animals with laboratory-confirmed disease and in a substantial proportion of seropositive asymptomatic animals, but not in the control samples. Additionally, the antigen was detected in the feces of animals with Johne's disease by ELISA. This study strongly suggests that Apa is a potential fecal biomarker of Johne's disease that could serve for immunodiagnosis.